Knowledge Retention of Scout Member Post Hands Only CPR Training Using CPR Pillow in Lubuklinggau City - Sapondra Wijaya; Wahyu Dwi Ari Wibowo; Andra Saferi Wijaya; Hendri Heriyanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Knowledge gained during CPR training can decline over time. Periodic training is needed to minimize the decline in knowledge. This study used the development of a CPR pillow as a learning medium with a low-cost, low-fidelity mannequin. A total of 72 subjects in this study were given CPR education and training. Measurements were taken 4 times, namely before training, the second immediately after training, then the third and fourth times within a 2-month period. The results showed an increase in average knowledge immediately after training and a decrease 2 months after training although not significant. The use of a CPR pillow can ultimately help maintain CPR knowledge to overcome the high cost of training related to mannequins.